KAJIAN FILOSOFIS KARAKTERISTIK WIRAUSAHA URANG SUNDA - Dedeng Abdul Gani Amruloh (Eqien - Jurnal Ekonomi dan Bisnis, 2019)
The purpose of this study is to combine conceptual work that combines Sundanese culture based on existing philosophy in the community with entrepreneurial characteristics from various entrepreneurial literature, from this research expected tobe carried out by Sundanese philosophy that encourages and improves Sundanese personality to have the functional as an entrepreneur. The research used descriptive qualitative method, with literature based on journals, magazines, and other relevant ones and conducting limited interviews relevant to the purpose of the study, the analysis used descriptive analysis by discussing with Sundanese society. The results of this study reveal the existence of Sundanese philosophy originating from various sources including oral culture related to the type of entrepreneurship, although not directly and explicitly to become an entrepreneur. Nevertheless, for the future the cultural approach as the basis for forming entrepreneurship is very necessary, including Sundanese entrepreneurship that are trained through the approach of philosophy and other teachings of Sundanese culture including Religion and the value of spirituality that can still be practiced by Sundanese people.